Exploring corrosion protection of mild steel by ionic liquid functionalized graphene oxide: Gravimetric, electrochemical, and surface studies - M.Alharbi; Ruby Aslam; Ajahar Khan; Khalid A. Alamry; Mahmoud A. Hussein; Yas Al-Hadeethi; Elena Bekyarova; S. Alqahtani (Results in Chemistry)
This work investigates the corrosion protective characteristics of graphene oxide functionalized with an ionic liquid, namely choline hexanoate, abbreviated as Ch-Hex/GO nanohybrid, for mild steel in 5% HCl solution. The performance of this nanohybrid was evaluated using a range of analytical methods, including weight loss measurement, electrochemical method, contact angle measurement, XPS, Atomic Force Microscopy (AFM), Scanning Electron Microscopy (SEM), and Energy Dispersive Spectroscopy (EDS). Using Fourier Transform Infrared Spectroscopy (FTIR), Transmission Electron Microscopy (TEM), and Raman analysis, the synthesis of Ch-Hex/GO was verified. An inhibitory efficiency reaching 85.75 % at a 100 ppm inhibitor concentration at 298 K was observed, which was further increased with increasing temperature, reaching 97.48 % at 323 K, suggesting a chemisorption mechanism. Assessments of inhibition performance throughout a range of immersion times, up to 144 hr, revealed a steady rise in efficiency up to 96 hr, followed by a minor decline while maintaining efficiencies above 85 %. The pronounced increases in polarization resistance (Rp) and reductions in corrosion current density (Icorr) indicated the strong adsorption of inhibitor molecules onto metal surface. In addition, the values of open circuit potential (OCP) and corrosion potential (Ecorr) were further evidence of a mixed inhibition mechanism. XPS and AFM/SEM analyses confirmed and supported these results, indicating the formation of protective layer on the steel surface.